Understanding episodic memory dynamics: Retrieval and updating mechanisms revealed by fMRI and tDCS - Dong-ni Pan; CuiZhu Lin; Ma Xin; Oliver T. Wolf; Gui Xue; Xuebing Li (NeuroImage)
This study investigates brain mechanisms in memory preservation and alteration using a three-phase design: memory encoding (Day 1), interference under fMRI (Day 2), and testing (Day 3). Thirty-one participants completed the core experiment, supplemented by a tDCS study (n = 118) targeting the visual cortex. Original memories were more susceptible to incorrect updating during old-background/new-object interference compared to relearning and no-retrieval conditions. Interference trials elicited heightened activation in the Inferior Parietal Lobe (IPL), Dorsolateral Prefrontal Cortex (DLPFC), and Dorsal Anterior Cingulate Gyrus (dACC) versus no-retrieval controls, and increased frontoparietal and Occipital Fusiform Gyrus (OFG) activation versus relearning. Analyzing interference trials by Day 3 outcomes revealed preserved memories correlated with stronger cingulo-opercular and frontoparietal activation (indicating effective conflict resolution), whereas updated memories showed elevated OFG activity (suggesting new sensory integration). Crucially, IPL/DLPFC activation during interference positively correlated with original memory accuracy, while OFG activation showed negative correlation. tDCS stimulation of the occipital cortex during memory reactivation significantly enhanced memory updating, confirming visual cortex involvement in contextual distortion. Findings demonstrate distinct neural profiles underlie memory outcomes: preserved memories require efficient conflict processing networks, while perceptual interference during reactivation promotes updates through sensory integration systems. This supports targeted neuromodulation approaches for memory modification, highlighting intervention potential through visual cortex engagement during critical memory phases.